Determinants Of Millenial Generation Intention In Indonesia In Cash Waqf Linked Sukuk - Muhamad Aliyul Adhim; Jeihan Ali Azhar (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2025)
This study aims to examine the factors influencing the intention of the millennial generation to participate in the Cash Waqf Linked Sukuk (CWLS) instrument in Indonesia. The research adopts the Theory of Planned Behavior (TPB), which includes three primary constructs—attitude, subjective norms, and perceived behavioral control—with trust serving as a moderating variable between attitude and intention. A purposive sampling technique was employed, resulting in 250 questionnaire responses, of which 194 met the sampling criteria. Data were analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with SmartPLS software. The findings indicate that trust strengthens the relationship between attitude and intention. Additionally, both attitude and perceived behavioral control have a positive and significant effect on millennials' intention to participate in CWLS, whereas subjective norms do not show a considerable influence. These results suggest the importance of enhancing financial literacy, information transparency, and accessibility to CWLS to foster trust and encourage active participation in cash waqf through sukuk among the millennial generation.